MODEL EPISTEMOLOGI TEOSOFI SUHRAWARDI AL-MAQTUL DALAM ILUMINASI - LUCKY DAMARA YUSUF (stit-islamic-village, 2021)
Concept of Islamic epistemology according to Suhrawardi Al-Maqtul is light which has the highest energy source. Why light because light is something that doesn't need to be defined and doesn't need to be explained, because it is obvious. Therefore he became the source or the highest level of Suhrawardi philosophy of illumination. This article will examine the views Yahya Suhrawardi gave a new direction in the development of Islamic thought, apart from his self-acknowledgment that bridges the knowledge given by Allah directly and indirectly but through several stages, but this is also due to his thinking which combines intuition and reason.